INTERACTIVE STRATEGIES IN EFL CLASSROOMS: A SYSTEMATIC LITERATURE REVIEW ON COMMUNICATIVE SKILL DEVELOPMENT - Amanda Salsabila; Resti Amelinda I. L; Zumiyati Zumiyati; Zaitun Qomariah (JPMUJ, 2025)
Communication competence in English is a key skill that is increasingly important in the era of globalization, especially for English as a Foreign Language (EFL) learners. This literature review aims to examine the effectiveness of interactive learning methods in improving EFL students' communication skills, with reference to sociocultural and interactionist theories. The research used a systematic review design of empirical studies published between 2013 and 2023. A thematic analysis of the selected literature revealed that interactive strategies such as role-playing, task-based learning, and utilization of digital platforms such as Quizizz consistently improved students' fluency, participation, and confidence in English. These approaches encourage meaningful interactions and active student engagement, which are crucial factors in language acquisition. However, challenges such as technological limitations and lack of teacher training remain barriers to implementation. This study emphasizes the importance of institutional support to optimize the pedagogical benefits of interactive approaches in EFL classrooms. The findings provide practical insights for educators in designing communication-focused learning in various educational contexts.